2022
DOI: 10.7554/elife.74387
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and nanoscale organization of the postsynaptic endocytic zone at excitatory synapses

Abstract: At postsynaptic sites of neurons, a prominent clathrin-coated structure, the endocytic zone (EZ), controls the trafficking of glutamate receptors and is essential for synaptic plasticity. Despite its importance, little is known about how this clathrin structure is organized to mediate endocytosis. We used live-cell and super-resolution microscopy to reveal the dynamic organization of this poorly understood clathrin structure in rat hippocampal neurons. We found that a subset of endocytic proteins only transien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…They observed that proteins contributing to the early phase of endocytosis mostly accumulate specifi cally at the periphery of the EZ. While other endocytic proteins, mostly involved in the later phase of endocytosis including vesicle scission, were more widely and centrally distributed at the EZ (Catsburg et al, 2022), consistent with observations at clathrin sheets in non-neuronal cells (Sochacki et al, 2017). Also, while some endocytic proteins such as CPG2 were found to contribute more generally to receptor internalization, others such as Endophilin-B2 were found specifi cally required for activity-induced, but not constitutive internalization (Loebrich et al, 2016).…”
Section: Novel Insights In Synaptic Tra Cking Of Mglurssupporting
confidence: 76%
See 2 more Smart Citations
“…They observed that proteins contributing to the early phase of endocytosis mostly accumulate specifi cally at the periphery of the EZ. While other endocytic proteins, mostly involved in the later phase of endocytosis including vesicle scission, were more widely and centrally distributed at the EZ (Catsburg et al, 2022), consistent with observations at clathrin sheets in non-neuronal cells (Sochacki et al, 2017). Also, while some endocytic proteins such as CPG2 were found to contribute more generally to receptor internalization, others such as Endophilin-B2 were found specifi cally required for activity-induced, but not constitutive internalization (Loebrich et al, 2016).…”
Section: Novel Insights In Synaptic Tra Cking Of Mglurssupporting
confidence: 76%
“…Also, while some endocytic proteins such as CPG2 were found to contribute more generally to receptor internalization, others such as Endophilin-B2 were found specifi cally required for activity-induced, but not constitutive internalization (Loebrich et al, 2016). Remarkably, the EZ undergoes activity-induced remodeling to accommodate long-term changes in synaptic strength (Catsburg et al, 2022). This suggests that reorganization of the EZ induced upon distinct synaptic activity patterns facilitates changes in endocytic rate of receptors modulating long-term synaptic plasticity, a hypothesis that would be interesting to test.…”
Section: Novel Insights In Synaptic Tra Cking Of Mglursmentioning
confidence: 99%
See 1 more Smart Citation
“…Strep-KDEL-Halo-Transferrin Receptor (TfR)-SBP (Halo-RUSH-TfR) (called RUSH-TfR in the text) was provided by Dr. Jennifer Lippincott-Schwartz (Weigel et al, 2021) (Addgene plasmid #166905) pF282-hEF1a-H2B-mNeonGreen-IRES-Puro x Tol2 was a gift from Dr. Judith Klumperman. Halo-Clathrin (Catsburg et al, 2022) was a gift from Dr. Harold MacGillavry.…”
Section: Methodsmentioning
confidence: 99%
“…The knock-in constructs of GluN1-GFP and clathrin light chain A-GFP (Willems et al, 2020), and dynamin2-GFP (Catsburg, Westra, van Schaik, & MacGillavry, 2022) were previously described. The knock-in construct for Nav1.2 was cloned in the pORANGE (Willems et al, 2020) and the gRNA used was: GGACAAAGGGAAAGATATCA.…”
Section: Dna Constructsmentioning
confidence: 99%